2018
DOI: 10.3390/nano8100800
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Self-supporting Bagasse Cellulose Nanofibrils Hydrogels Induced by Zinc Ions

Abstract: Cellulose hydrogels are often prepared from native cellulose through a direct cellulose dissolution approach that often involves tedious process and solvent recovery problems. A self-supporting cellulose hydrogel was prepared by gelation of the TEMPO-oxidized bagasse cellulose nanofibrils (CNF) triggered by strong crosslinking between carboxylate groups and Zn2+. TEMPO process was used to generate negatively charged carboxylate groups on CNF surface to provide a high binding capability to Zn2+. Three TEMPO-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Thus, nanocellulose hydrogels have great potential as a smart packaging material. Lu et al (2018) showed a CNF hydrogel indicator that was exposed to fresh-cut fruits [131]. The study showed that the changes in color from dark green, which indicated a still fresh fruit, to an orange yellow that indicated that it had already spoiled after two days, as shown in Figure 8.…”
Section: Potential Applications Of Opefb Nanocellulose Hydrogelmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, nanocellulose hydrogels have great potential as a smart packaging material. Lu et al (2018) showed a CNF hydrogel indicator that was exposed to fresh-cut fruits [131]. The study showed that the changes in color from dark green, which indicated a still fresh fruit, to an orange yellow that indicated that it had already spoiled after two days, as shown in Figure 8.…”
Section: Potential Applications Of Opefb Nanocellulose Hydrogelmentioning
confidence: 97%
“…Color changes detected by the cellulose nanofibrils hydrogel indicator. The figure above was adapted with permission from the cited reference[131].…”
mentioning
confidence: 99%
“…The surface configuration of the CNF film exhibited a uniform network structure, which indicated that the CNFs distributed randomly on the surface with no large-scale agglomeration, [33] as shown in Figure 6A. Nevertheless, as shown in Figure 6B, the CNFs/RGO (18) composite film displayed an extremely coarse surface, and the graphene lamellae with wrinkles replaced the network structure.…”
Section: Characterization Of the Cnf Film And Cnfs /Go (N) And Cnfsmentioning
confidence: 94%
“…The binding of calcium ions to CSP molecules can inhibit this process (Zhang, Zhao, Lai, Chen, & Yang, 2018). In bagasse, zinc ions can induce the formation of cellulose nanofibrillar hydrogels (Lu, Liu, Liu, & Wu, 2018). Moreover, gelation of fish proteins has attracted interest due to its application in structured food products.…”
Section: Interaction Phenomena and Complexesmentioning
confidence: 99%